Pemberdayaan Ekonomi Perempuan Melalui Program Bank BTPN Syariah: Studi Literatur - Moch. Khoirul Anwar; Wulandari, Maulidia; Maryam Bte Badrul Munir (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Women's economic empowerment has emerged as a central issue in sustainable development. BTPN Syariah, a pioneer in inclusive finance, has been actively involved in empowering women economically through various innovative programs. This research delves into the effectiveness of the business coaching programs and murabahah financing offered by BTPN Syariah. A literature review indicates that these two programs complement each other and have a significant impact on enhancing women's economic capacity. Comprehensive business coaching, ranging from technical training to business network development, has successfully boosted the self-confidence and management skills of women entrepreneurs. Meanwhile, murabahah financing, aligned with sharia principles, has provided fairer and more affordable access to capital, fostering sustainable business growth. The combination of these two programs has not only increased family income but also contributed to poverty reduction, gender inequality reduction, and local economic growth. This study aims to conduct an in-depth analysis of the effectiveness of the business coaching and murabahah financing programs offered by BTPN Syariah in the context of women's economic empowerment through a literature review.